Examining Political Parties' Record on Refugees and Asylum Seekers in UK Party Manifestos 1964–2019: The Rise of Territorial Approaches to Welfare?. Issue 4 (2nd October 2021) - Chaney, Paul
Abstract: This study addresses a key lacuna by analyzing political parties' formative policy record on refugees' and asylum seekers' welfare in party manifestos for state-wide and meso-elections in the UK, 1964–2019. The findings confirm relational contrasts in issue-prioritization and the framing of pledges – between parties and across polities. The wider significance of this lies in underlining the need to examine the formative, electoral phase of refugee and asylum-seeker policy-making; and showing how the move to a multi-level electoral system combines with regional party politics to drive the territorialization of RAS welfare in federal and union states.